A1C diagnostic accuracy for Type 2 diabetes mellitus in North Mexico - Luis F Pérez-García; Luis Villela; Salvador B Valdivinos-Chávez; Adria Tinoco; Ignacio Rangel-Rodríguez (Instituto Nacional de Salud Pública, 2019)
[Not available]